Aspek Feminist Legal Theory dalam Peraturan Perundang-undangan di Indonesia - Rakia, A. Sakti R.S.; Hidaya, Wahab Aznul (Amsir Law Journal, 2022)
The study of the feminist paradigm which substantially discusses equality between men and women, in law raises a school of thought in feminist legal theory. In general, the discourse on feminist legal theory focuses on the discussion that the dominance of men has resulted in the formation of legal norms with a masculine nuance so that the role of women is still subordinated to men. This study aims to explore the extent to which aspects of Feminist Legal Theory are reflected in the laws and regulations in Indonesia. This research is a normative-juridical research with a conceptual approach and a theoretical approach. The results of this study indicate that the issue of feminism is spread in a number of laws and regulations in Indonesia, but with still overlapping regulations when analyzed based on feminist legal theory.